Safety of temporary pacemaker wires. (June 2019) - Elmistekawy, Elsayed
It is routine practice to insert temporary pacemaker wires in cardiac surgery patients. In selected patients, temporary pacemakers are helpful in the management of cardiac surgery patients intra- and postoperatively. Although this practice is generally safe, a small percentage of patients may have complications at the time of insertion, during pacing postoperatively, at the time of pacemaker wire removal, or if temporary wires are retained inside the body. This review will shed some light on the safety issues of temporary pacemaker wire usage.